Synthesis, Characterization and Biological Studies of Ether–Based Ferrocenyl Amides and their Organic Analogues - Sana Waseem Abbasi; Naveed Zafar Ali; Martin Etter; Muhammad Shabbir; Zareen Akhter; Stacey J. Smith; Hammad Ismail; Bushra Mirza (Crystals, 2020)
Ferrocenyl amides (FB1-FB13) and their organic analogues (BZ1-BZ13) were prepared by a low-temperature condensation method. Ferrocenyl amides were synthesised using 4-ferrocenylbenzoyl chloride and ether-based amines and diamines. Benzoyl chloride was used to synthesise organic analogues by reacting with various amines. The synthesised compounds were characterised by elemental, spectroscopic (FT-IR and NMR) and single crystal X-ray diffraction methods. Crystal structures of the representative organic analogues (BZ2 and BZ6) were solved by single crystal X-ray diffraction. BZ2 crystallises in the triclinic space group P <semantics> <mover accent="true"> 1 ¯ </mover> </semantics> with a unit cell volume of V = 1056.6(3) Å3 and with two formula units per unit cell. Whereas BZ6 assembles in the orthorhombic space group Pbca with four formula units per unit cell and a unit cell volume of V = 1354.7(2) Å3. Spectral studies confirmed the presence of amide linkages in the synthesised compound with a strong N—H·····O=C hydrogen bonding network established between amide groups of neighbouring molecular scaffolds further stabilising the molecular stacking in accordance with the archetypal crystal structures. The bioactive nature of each compound was assessed by DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging activity, hydrogen peroxide scavenging activity and total antioxidant activity. Antidiabetic, anticholinesterase enzyme inhibition tests, as well as antibacterial activities, were performed showing significant biological activity for ferrocenyl amides as compared to their organic analogues.